2006
DOI: 10.1158/0008-5472.can-05-1862
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to UV-Induced Skin Carcinogenesis in Polymerase η–deficient Mice

Abstract: Xeroderma pigmentosum variant (XPV) patients with mutations in the DNA polymerase H (pol h) gene are hypersensitive to sunlight and have greatly increased susceptibility to sunlight-induced skin cancer. Consistent with the ability of Pol H to efficiently bypass UV light-induced cyclobutane pyrimidine dimers, XPV cells lacking Pol H have diminished capacity to replicate UV-damaged DNA and are sensitive to UV light-induced killing and mutagenesis. To better understand these and other Pol H functions, we generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 38 publications
6
74
1
Order By: Relevance
“…The increasing incidence of tumors in mice lacking only one Polh allele indicates that heterozygous XP-V patients may be more susceptible to cancer than are normal individuals that are chronically exposed to sunlight. Similar results for UV-induced skin carcinogenesis in an independently generated mouse deficient for a single allele of Pol were recently reported by Lin et al (36).…”
Section: Polh-deficient Mice As An Xp-v Modelsupporting
confidence: 89%
“…The increasing incidence of tumors in mice lacking only one Polh allele indicates that heterozygous XP-V patients may be more susceptible to cancer than are normal individuals that are chronically exposed to sunlight. Similar results for UV-induced skin carcinogenesis in an independently generated mouse deficient for a single allele of Pol were recently reported by Lin et al (36).…”
Section: Polh-deficient Mice As An Xp-v Modelsupporting
confidence: 89%
“…However, in a 2-y study, no increase in the incidence of tumors of any type was found with pol η KO (pol η −/− ) mice (15). Instead, we found pol η −/− mice develop metabolic abnormalities that induce obesity.…”
contrasting
confidence: 71%
“…However,ˆbroblasts from these mice showed enhanced sensitivity to UV, and all of the Polh-deˆcient mice developed skin tumors after UV-irradiation. These results conˆrm that Polh prevents UVinduced cell death and skin cancer by catalyzing the accurate bypass of CPDs in mice as well as in humans (73,74).…”
Section: In Vivo Functions Of Polhsupporting
confidence: 56%